Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: 1. Women’s work in the military sector and its impact on family relations – A descriptive study on a sample of families in Jeddah – Ms. Reem Abdulrahman Al-Zahrani, Ms. Ramiyah Khader Al-Rami, Dr. Samira Saad El-Din El-Maghribi 2. Social Dominance in Saudi Narration, Sociological Approach in Selected Novels Ms. Shoroq Abdullah Althumairi 3. Simulating The Temporal and Spatial Patterns of Urban Growth in Abha Using the Markov-CA Combined Statistical Model During The Period from 2000 to 2040 Ms. Eman Mohammed Ali Alqahtani 4. Housing at Risk of Collapse and its Effects on the Health Situation of Residents and Management Policies: The Case of the Old City of Salé in Morocco Dr. Nezha Arabi, Dr. Mohamed Aneflouss 5. Evaluating the spatial suitability of primary schools for boys in the city of Makkah using multi-criteria geographic information systems Ms. Abdullah Abdul-Aziz Yamani, Dr. Morshed Muayoud Al-Salmi 6. The transportation system and its role in the relations between urban centers and rural areas in the Inaoun Basin Depression Dr. Ali Neddama, Dr. Jaouad El-Bazoui, Dr. Abdelouahed Bouberria 7. Improving Iraqi English Learners’ Ability to Develop and Support Claims in Argumentative Writing Ms. Dua’a Ali Tahir, Asst-Prof. Sawsan A. Qasim 8. Cultural Identity Formations in Arabic Children’s Literature Dr. Rafea Saeid Yehia